A Case of Chronic Otitis Media Complicated with Cerebellar Abscess (Bangladesh Journal of Medical Science, 2018)
Introduction:Intracranial complications are a known sequale of chronic otitis media. Meningitis is the most common intracranial complication, followed by otogenic brain abscess. Temporal lobe abscesses are more frequently reported in the literature as compared to cerebellar abscesses.Case Report: We present a case of chronic otitis media with cerebellar abscess that need drainage of the abscess twice. The mastoidectomy was done few days later once the patient stable.Conclussion: The case report highlights the increasing incidence of cerebellar abscess as an intracranial complicationwith literatures review. Besides that, we also discuss about the appropriate timing of ear surgery and neurosurgical drainage, as well as its outcome.Bangladesh Journal of Medical Science Vol.17(1) 2018 p.149-151